A Rod‐Packing Hydrogen‐Bonded Organic Framework with Suitable Pore Confinement for Benchmark Ethane/Ethylene Separation. (26th March 2021) - Zhang, Xu; Wang, Jia‐Xin; Li, Libo; Pei, Jiyan; Krishna, Rajamani; Wu, Hui; Zhou, Wei; Qian, Guodong; Chen, Banglin; Li, Bin
Abstract: For the separation of ethane from ethylene, it remains challenging to target both high C2 H6 adsorption and selectivity in a C2 H6 ‐selective material. Herein, we report a reversible solid‐state transformation in a labile hydrogen‐bonded organic framework to generate a new rod‐packing desolvated framework (ZJU‐HOF‐1) with suitable cavity spaces and functional surfaces to optimally interact with C2 H6 . ZJU‐HOF‐1 thus exhibits simultaneously high C2 H6 uptake (88 cm 3 g −1 at 0.5 bar and 298 K) and C2 H6 /C2 H4 selectivity (2.25), which are significantly higher than those of most top‐performing materials. Theoretical calculations revealed that the cage‐like cavities and functional sites synergistically "match" better with C2 H6 to provide stronger multipoint interactions with C2 H6 than C2 H4 . In combination with its high stability and ultralow water uptake, this material can efficiently capture C2 H6 from 50/50 C2 H6 /C2 H4 mixtures in ambient conditions under 60 % RH, providing a record polymer‐grade C2 H4 productivity of 0.98 mmol g −1 . Abstract : A rod‐packing microporous hydrogen‐bonding framework with functional surfaces and suitable cavity spaces for C2 H6 uptake exhibited simultaneously high capacity and C2 H6 /C2 H4 selectivity (see picture). The excellent C2 H6 /C2 H4 separation occurred with record‐high C2 H4 productivity of 0.98 mmol g −1 under high humidity and ambient conditions.